The outlaws. Series one [videorecording (DVD)] - Merchant, Stephen; Merchant, Stephen; Butler, John, 1972-; Unsworth, Emma Jane; Lalwani, Nikita, 1973-; Barreto, Rhianne; Boyd, Darren, 1971-; Cole, Gamba; Gunning, Jessica; Tomlinson, Eleanor, 1992-; Walken, Christopher, 1943- (BBC, 2023)
In this sharp new comedy-drama, an unlikely group of lawbreakers is forced together in a community payback project. When seven strangers are thrown together in a community service scheme, they realize they couldn't be more different. Having broken the law, in their hometown of Bristol, is the one thing they have in common. As new friendships emerge, dark secrets are revealed. And when the group gets drawn into dangerous criminal activity, they must break down the barriers between them, before they can fight for what's right. Combining crime thriller, character study, and comedy, The Offenders is a state-of-the-nation commentary with humor and heart.